Antioxidant Potential, Anti-Diabetes, and Toxicity of Aceh Cinnamon Extract (Cinnamomum burmannii) - Husna, Fauzul; Suhaila, Suhaila; Syahrizal, Dedy; Zulkarnain, Zulkarnain; Washilah, Hasya; Sahriana, Ananda Putri (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
Indonesia as a mega biodiversity country must take a role in the development of herbal-based medicine. Cinnamon is often used empirically to overcome various health problems, especially diabetes. This study aims to assess the effectiveness of Aceh cinnamon extract as an antioxidant and antidiabetic in vitro and to evaluate the toxicity of the extract. Cinnamons, obtained from coffee plantations in Simpang Teritit, Bener Meriah, Aceh, were macerated with 96% ethanol for extraction. Furthermore, the extract phytochemical content was determined qualitatively, semiquantitatively (GC-MS), and quantitatively (levels of phenols, flavonoids, and total tannins). The toxicity level was measured by an acute toxicity test based on the OECD and the BSLT assay. The effectiveness as an antioxidant and anti-diabetes was determined in vitro by the DPPH inhibition method and α-glucosidase inhibition. The results of this study showed that cinnamon extract contains alkaloids, flavonoids, polyphenols, tannins, quinones, saponins, and triterpenoid compounds. The total amount of phenol, flavonoid, and tannin extract levels were 66.34 mg GAE/gr, 80.52 mg QE/gr, and 566.33 mg AT/gr. The IC50 extract value against DPPH was 16.07 ppm and against the enzyme, α-glucosidase was 123.52 ppm. In the acute toxicity test, the value of LD50 ≥15 grkg BWW was obtained and in the toxicity test with BSLT, LC50 extract was 350.57 ppm. Aceh cinnamon extract (Cinnamomum burmannii) has LD50 > 15 gr/kg BW and LC50 value >500 ppp which is categorized as a practically non-toxic ingredient and low toxicity agent with strong antioxidant activity and moderate antidiabetics.